Covering a Graph with Clubs - Dondi, Riccardo; Mauri, Giancarlo; Sikora, Florian; Zoppis, Italo (Journal of Graph Algorithms and Applications, 2019)
Finding cohesive subgraphs in a network has been investigated in many network mining applications. Several alternative formulations of cohesive subgraph have been proposed, a notable one of them is s-club, which is a subgraph whose diameter is at most s. Here we consider a natural variant of the well-known Minimum Clique Cover problem, where we aim to cover a given graph with the minimum number of s-clubs, instead of cliques. We study the computational and approximation complexity of this problem, when s is equal to 2 or 3. We show that deciding if there exists a cover of a graph with three 2-clubs is NP-complete, and that deciding if there exists a cover of a graph with two 3-clubs is NP-complete. Then, we consider the approximation complexity of covering a graph with the minimum number of 2-clubs and 3-clubs. We show that, given a graph G=(V,E) to be covered, covering G with the minimum number of 2-clubs is not approximable within factor O(|V|^1/2 -ε), for any ε>0, and covering G with the minimum number of 3-clubs is not approximable within factor O(|V|^1 -ε), for any ε>0. On the positive side, we give an approximation algorithm of factor 2|V|^1/2^3/2 |V| for covering a graph with the minimum number of 2-clubs.